# Short theorem prover

### From HaskellWiki

BrettGiles (Talk | contribs) (Spelling and format) |
m |
||

(One intermediate revision by one user not shown) | |||

Line 1: | Line 1: | ||

− | + | Theorem prover in 625 characters of Haskell | |

<haskell> | <haskell> | ||

Line 19: | Line 19: | ||

m=(a?a:)$map l$catMaybes$liftM2(uncurry.j.g(*2))m[((((a?b?c) | m=(a?a:)$map l$catMaybes$liftM2(uncurry.j.g(*2))m[((((a?b?c) | ||

?(a?b)?a?c)?(d?e?d)?f),f),((a?b),(c?a)?c?b)] | ?(a?b)?a?c)?(d?e?d)?f),f),((a?b),(c?a)?c?b)] | ||

− | main= | + | main=readLn>>=print.(`elem`m) |

</haskell> | </haskell> | ||

You are not expected to understand that, so here is the explanation: | You are not expected to understand that, so here is the explanation: | ||

Line 90: | Line 90: | ||

facts = nub $ (axiom:) $ map canon $ catMaybes $ liftM2 deduce facts rules | facts = nub $ (axiom:) $ map canon $ catMaybes $ liftM2 deduce facts rules | ||

− | main= | + | main=readLn>>=print.(`elem`facts) |

</haskell> | </haskell> | ||

[[Category:Code]] | [[Category:Code]] |

## Latest revision as of 08:23, 13 December 2009

Theorem prover in 625 characters of Haskell

import Monad;import Maybe;import List infixr 9 ? (?)=(:>);z=Just;y=True data P=A Integer|P:>P deriving(Read,Show,Eq) [a,b,c,d,e,f]=map A[1,3..11] g=h(?).(A.) h f z(A x)=z x h f z(x:>y)=h f z x`f`h f z y i p(A i)j=p&&i==j i p(a:>b)j=i y a j||i y b j j(A l)s(A k)|i False s l=Nothing|l==k=z s|y=z$A k j f@(A i)s(a:>b)=liftM2(?)(j f s a)(j f s b) j f s@(A i)p=j s f p j(a:>b)(c:>d)p=let u=j a c in join$liftM3 j(u b)(u d)(u p) l x=g(toInteger.fromJust.flip elemIndex (h union (:[]) x))x m=(a?a:)$map l$catMaybes$liftM2(uncurry.j.g(*2))m[((((a?b?c) ?(a?b)?a?c)?(d?e?d)?f),f),((a?b),(c?a)?c?b)] main=readLn>>=print.(`elem`m)

You are not expected to understand that, so here is the explanation:

First, we need a type of prepositions. Each A constructor represents a prepositional variable (a, b, c, etc), andtype U = Integer data P = A U | P:>P deriving(Read,Show,Eq) infixr 9 :>

To prove theorems, we need axioms and deduction rules. This theorem prover is based on the Curry-Howard-Lambek correspondence applied to the programming language Jot (http://ling.ucsd.edu/~barker/Iota/#Goedel). Thus, we have a single basic combinator and two deduction rules, corresponding to partial application of the base case and two combinators of Jot.

axiom = A 0:>A 0 rules = let[a,b,c,d,e,f]=map A[1,3..11]in[ (((a:>b:>c):>(a:>b):>a:>c):>(d:>e:>d):>f):>f, (a:>b):>(c:>a):>c:>b]

We will also define foogomorphisms on the data structure:

pmap :: (U -> U) -> P -> P pmap f = pfold (:>) (A .f) pfold :: (a -> a -> a) -> (U -> a) -> P -> a pfold f z (A x) = z x pfold f z (x:>y) = pfold f z x`f`pfold f z y

cnt p(A i) j = p && i == j cnt p(a:>b) j = cnt True a j || cnt True b j

The deduction steps are performed by a standard unification routine:

unify :: P -> P -> P -> Maybe P unify (A i) s (A j) | cnt False s i = Nothing | i == j = Just $ s | otherwise = Just $ A j unify f@(A i) s (a:>b) = liftM2 (:>) (unify f s a) (unify f s b) unify f s@(A i) pl = unify s f pl unify (a:>b) (c:>d) pl = let u = unify a c in join $ liftM3 unify (u b) (u d) (u pl)

We need to renumber terms to prevent name conflicts.

fan (A x) = A (x*2) fan (x:>y)= fan x:> fan y

Make a deduction given a rule, by setting the LHS of the rule equal to the state and taking the RHS of the rule.

deduce t r = let (a:>b)=r in unify (fan t) a b

Canonicalize the numbers in the rule, thus allowing matching.

canon :: P -> P canon x = pmap (toInteger . fromJust . flip elemIndex ( allvars x )) x allvars :: P -> [U] allvars = pfold union (:[])

Given this, we can lazily construct the list of all true statements:

facts = nub $ (axiom:) $ map canon $ catMaybes $ liftM2 deduce facts rules main=readLn>>=print.(`elem`facts)